Emotional intelligence and intercultural growth: Examining affective dimensions in the EFL public speaking classroom - Anugerah Febrian Syam (Yayasan Mitra Persada Nusantara, 2026)
Although Emotional Intelligence (EI) is often associated with communication success, EFL studies tend to position it as an individual psychological attribute and have not yet explored its affective dimension in the process of intercultural growth. This research aims to reconstruct EI as a relational practice in EFL public speaking classes. The study used an ethnographic approach based on an interpretivist paradigm, involving 24 EFL students at a private university. Data were collected over one semester through participant observation, video recordings of presentations, peer feedback sessions, reflective journals, and field notes. Analysis was conducted abductively and iteratively, combining open coding, micro-ethnography of interaction, and theoretical coding. The findings indicate that speech anxiety, embodied confidence, interactional empathy, and negotiation of cultural voice form a relational ecology of affect that fosters intercultural becoming. EI does not emerge as a stable competency, but rather as a situated and co-constructed affective practice. This study concludes that EFL public speaking is an arena for intercultural transformation rooted in emotional engagement rather than merely rhetorical mastery.